Reflection on ozonation within a wastewater biotreatment process for synthetics degradation - van Leeuwen, J. (Hans); Barnard, James L.; Koziel, Jacek A.; Ellis, Timothy G. (Frontiers in Environmental Chemistry, 2025)
The 8-billion human population on this planet produces 700,000 m3 wastewater per minute, most of which is treated, usually with a bacterial process, to lower environmental impact. Synthetic substances in wastewater from industry, e.g., agrochemicals, pesticides, and textile dyes are difficult to degrade during such biological treatment. These substances degrade the environment, discolor water, and kill or inhibit aquatic organisms. Removal of synthetic compounds currently involves advanced and more expensive technologies than just biological treatment. The body of work summarized in this article was aimed at improving biological wastewater treatment by breaking down non-biodegradable substances with ozone. What was novel is that the ozone was not introduced conventionally either before or after, but during biological treatment. The work describes how ozone could be used within activated sludge treatment to oxidize undesirable compounds to substances that are either innocuous or biodegradable directly in the same reactor through bacterial action. Research focused on removing dyes, methylene blue and Orange II, cyanide as test substances, and using ozonation within an activated sludge process was found to be quite effective. The choice of test substances was based both on how commonly such substances are contained in industrial wastewater and the ease to identify byproducts. There is growing evidence that a powerful disinfectant such as ozone does not necessarily inhibit beneficial organisms when used directly in a biological process. This is probably due to reaction kinetics. The review showed that it was indeed possible to degrade certain undesirable compounds, such as methylene blue, Orange II, and a range of synthetic organic compounds by combined ozone oxidation and biodegradation within the bioprocess, all without serious inhibition of useful organisms, even protecting these by lowering the toxicity of some target compounds. If an oxidation reaction is fast, the build-up of an ozone residual in solution is minimized, thereby substantially decreasing the disinfecting power the ozone might have had, as disinfection is a function of both disinfectant concentration and exposure time. By cutting both the concentration and shortening the exposure time with rapid competing reactions, the microbes are shielded from ozone.